The history of simulation in medical education and possible future directions - Bradley, Paul (Medical education, 2006)
Introduction  Clinical simulation is on the point of having a significant impact on health care education across professional boundaries and in both the undergraduate and postgraduate arenas. Scope of simulation  The use of simulation spans a spectrum of sophistication, from the simple reproduction of isolated body parts through to complex human interactions portrayed by simulated patients or high‐fidelity human patient simulators replicating whole body appearance and variable physiological parameters. Growth of simulation  After a prolonged gestation, recent advances have made available affordable technologies that permit the reproduction of clinical events with sufficient fidelity to permit the engagement of learners in a realistic and meaningful way. At the same time, reforms in undergraduate and postgraduate education, combined with political and societal pressures, have promoted a safety‐conscious culture where simulation provides a means of risk‐free learning in complex, critical or rare situations. Furthermore, the importance of team‐based and interprofessional approaches to learning and health care can be promoted. Conclusion  However, at the present time the quantity and quality of research in this area of medical education is limited. Such research is needed to enable educators to justify the cost and effort involved in simulation and to confirm the benefit of this mode of learning in terms of the outcomes achieved through this process.